INTANGIBLE - Bortesi Longhi, Luis (2014)
There is a progressive and increasingly widespread trend in intangibles, consisting of the dematerialization of the communications, financial assets, trade, and in general, of human relationships. A particular case is that concerning this investigation is that of the “Intangible Assets” which are becoming larger and importance. Traditionally, intangible assets were limited to tra-demarks, patents and franchises, but today, covering many more aspects that enrich the value of the orga-nization. For starters, making a simple analogy, we could say that intangible assets are to be equivalent to the “spirit” or “sympathy” that the organization possesses and confers superiority and prestige. Many are the coordinates that can be analyzed with respect to intangibles, but an aspect of great interest is that concerning holism in the organization. Indeed, holism is the virtue by which “the whole is greater than the sum of its parts” expressed in other words, the organizational set has greater systemic importance that each individual component provides or produces.